(untitled) (Media Kesehatan Masyarakat Indonesia, 2023)
Stress is a condition of worry or mental tension caused by a difficult situation, often referred to as pressure. Meanwhile, resilience comprises active and distinct biological processes that protect organisms from the effects of stress. The COVID-19 pandemic has significantly impacted mental health, specifically among adolescents navigating a transitional period. Therefore, this study aimed to determine the relationship between stress and resilience among adolescents student during the COVID-19 pandemic. An analytic cross-sectional design was used and the study was conducted between February to July 2021. The subjects comprised 238 people from 22 MAN in the Jabodetabek area, selected through Cluster Random Sampling. Primary data were obtained by filling out the 42-item Depression Anxiety Stress Scale (DASS-42) and Miller Smith Rating Scale for Stress Tolerance (MSRS-ST) online questionnaires through the Google form application. Furthermore, data were analyzed using Chi-square and Multiple logistics regression tests. The results showed that the majority of respondents totaling 185 (77.7%) had high stress levels with 202 (84.9%) having low resilience. There was a significant relationship between stress levels and resilience as demonstrated by p-value = 0.0002. The variable “difficulty in relaxing” had a 0.13 times potential impact as a factor associated with stress levels. On the other hand, the variable “not drinking alcohol” was found to have a 16.77 times higher potential to be a factor associated with resilience.